2016
DOI: 10.1111/sjtg.12134
|View full text |Cite
|
Sign up to set email alerts
|

Gender and local soil knowledge: Linking farmers' perceptions with soil fertility in two villages in the Philippines

Abstract: Scientists often turn to farmers to understand soil management. This process reveals differences and overlaps between local and scientific soil knowledge but rarely considers women and gender issues. This paper examines men's and women's local knowledge of soils in upland, smallholder farms in two villages in Mindanao, the Philippines, using focus group discussions, semi‐structured household interviews, field visits, GIS and soil testing. Farmers' field areas were calculated and delineated based on their perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several studies have used qualitative research in environmental management (Failing, Gregory, & Harstone, 2007;Li, Woltjer, van den Brink, & Li, 2016) and soil sciences (Barbero-Sierra, Ruíz Pérez, Marqués Pérez, Álvarez González, & Cruz Maceín, 2018;Bouma, Kwakernaak, Bonfante, Stoorvogel, & Dekker, 2015;Christie, Parks, & Mulvaney, 2016;Ingram, Fry, &Mathieu, 2010 andOudwater &Martin, 2003). In this study, the workshop consultations and the reports (Sturel et al, 2018) were semi-structured to facilitate the data collection and processing required for descriptive statistics and data analysis.…”
Section: Data Collection Harmonization and Analysismentioning
confidence: 99%
“…Several studies have used qualitative research in environmental management (Failing, Gregory, & Harstone, 2007;Li, Woltjer, van den Brink, & Li, 2016) and soil sciences (Barbero-Sierra, Ruíz Pérez, Marqués Pérez, Álvarez González, & Cruz Maceín, 2018;Bouma, Kwakernaak, Bonfante, Stoorvogel, & Dekker, 2015;Christie, Parks, & Mulvaney, 2016;Ingram, Fry, &Mathieu, 2010 andOudwater &Martin, 2003). In this study, the workshop consultations and the reports (Sturel et al, 2018) were semi-structured to facilitate the data collection and processing required for descriptive statistics and data analysis.…”
Section: Data Collection Harmonization and Analysismentioning
confidence: 99%
“…Crossland et al (2018), reported different spatial assessment of where degradation was occurring in landscapes among men and women in Ethiopia attributed largely to their access and control over different land areas. Other factors that may influence knowledge and manage-ment practice are gender-differentiated land-use decisions, land use strategies, preferences and motivations (Christie et al, 2016;Villamor et al, 2014a). Other literature (Villamor et al, 2014b) further indicates that men and women's risk taking and access to innovation for land-use decision making may be different.…”
Section: Gendered Soil Knowledge and Managementmentioning
confidence: 99%
“…Even within a single landscape, previous studies have not assessed indicators of soil quality along slopes despite their importance in land degradation. Research on gender and farmers' knowledge has mostly focused on the soil fertility component of soil quality (Christie et al, 2016) and has not assessed whether understanding of soil quality by gender influences soil management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental knowledge and expertise are gendered (Christie et al 2016;Fortmann 1996), gleaned from people's "daily management of their living landscape" (Rocheleau et al 1996, p. 6). Failing to incorporate such gendered differences into development objectives can hinder the implementation of these agricultural practices, as well as exacerbate preexisting gender inequalities.…”
Section: Introductionmentioning
confidence: 99%